Urea based straw treatments for dairy cattle feeding management under farmers’ condition in Chitwan, Nepal - Paudel, D. P.; Dhakal, R.; Bhattarai, N. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was conducted at Gitanagar VDC of Chitwan during May to August 2012, to find the effect of chopped and un-chopped rice straw in relation to with/ without treatment of urea (4%) on milk yield and its composition. Repeated Measure Design (RMD) was conducted in 8 cows and four treatments namely; T1 (un-chopped straw), T2 (chopped straw), T3 (un-chopped straw with urea solution @ 4%) and T4 (chopped straw with urea solution @ 4%) providing all four treatments to each cow at an interval of 15 days to match with the design. The samples of treatments were analyzed for CP, EE, CF, Moisture level, and total ash content. Urea treated rice straw consumption was significantly different (p<0.05) among treatments. The average uptake of rice straw in T1, T2, T3 and T4 was found to be 3.39, 3.73, 3.81 and 3.9 kg/cow/day respectively. Similarly, milk yield from urea treated chopped rice straw was found significantly different (p<0.01) among other treatments. The average milk yield in four treatments T1, T2, T3 and T4 was found to be 9.449, 9.697, 10.011 and 10.264 liters/cow/day. In milk composition, urea treated rice straw had positive impact on increment of protein and fat % which was significantly different (p<0.01) and (p<0.05) respectively. While SNF, lactose, density, solubility, freezing point were statistically similar (p>0.05). Net income/cow was higher (Rs. 86.912) in T4 than other treatments. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 35-40